2011
DOI: 10.1016/j.febslet.2011.08.041
|View full text |Cite
|
Sign up to set email alerts
|

c-Fos regulates hepatitis C virus propagation

Abstract: a b s t r a c tHepatitis C virus (HCV) RNA replication requires cellular factors as well as viral non-structural proteins (NS protein). Using small interfering RNA (siRNA) library screening, we previously identified c-Fos as a host factor involved in HCV propagation. In the present study, we demonstrated that silencing of c-Fos expression resulted in decrease of HCV propagation in cell culture grown HCV (HCVcc)-infected cells; whereas overexpression of c-Fos significantly increased HCV propagation. We further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…9B) at 3% O 2 , together with oxidative stress-and ROS-related genes (see Table S2 in the supplemental material) that may contribute to oncogene induction. Among the induced oncogenes, FOS, MYC, SRC, and AKT have been already shown to directly activate glucose-related transporter and glycolytic gene promoters independently of HIFs (47,(57)(58)(59)(60)(61)(62) and, in addition, have been reported to stimulate HCV replication through either association with viral nonstructural proteins or other ways of action not completely defined (71,(79)(80)(81)(82)(83). In fact, our results confirmed the HIFindependent transcriptional activation of FOS and SRC (see Fig.…”
Section: Discussionsupporting
confidence: 80%
“…9B) at 3% O 2 , together with oxidative stress-and ROS-related genes (see Table S2 in the supplemental material) that may contribute to oncogene induction. Among the induced oncogenes, FOS, MYC, SRC, and AKT have been already shown to directly activate glucose-related transporter and glycolytic gene promoters independently of HIFs (47,(57)(58)(59)(60)(61)(62) and, in addition, have been reported to stimulate HCV replication through either association with viral nonstructural proteins or other ways of action not completely defined (71,(79)(80)(81)(82)(83). In fact, our results confirmed the HIFindependent transcriptional activation of FOS and SRC (see Fig.…”
Section: Discussionsupporting
confidence: 80%
“…For dual luciferase reporter assay, Huh7.5 cells were transfected with 20 nM of the indicated siRNAs for 24 h and then transfected with pRL-HL plasmid together with beta-galactosidase plasmid, as we reported previously [11]. For HCV reporter assay, Huh7.5 cells were electroporated with 10 lg of in vitro transcribed JFHLuc RNA and treated with tylophorine for the indicated time points.…”
Section: Luciferase Replication Assaysmentioning
confidence: 99%
“…4A. Huh7.5 cells transfected with siRNAs were co-transfected with pRL-HL [11] and b-galactosidase plasmid, and then the luciferase activity was determined. We demonstrated that knockdown of CycA2 had no effect on HCV IRES-dependent translation (Fig.…”
Section: Cyca2 Is Involved In the Genome Replication Stage Of Hcv Lifmentioning
confidence: 99%
“…For the dual-luciferase reporter assay, Huh7.5 cells were transfected with 25 nM SCD1 siRNA or negative siRNA for 48 h and then transfected with pRL-HL plasmid and pCH110 reference plasmid as described previously (19). For the inhibitor assay, Huh7.5 cells transfected with the indicated plasmids were incubated with various dosages of SCD1 inhibitor.…”
Section: Methodsmentioning
confidence: 99%